2012
DOI: 10.1180/minmag.2012.076.5.13
|View full text |Cite
|
Sign up to set email alerts
|

Bond topology and structure-generating functions: graph-theoretic prediction of chemical composition and structure in polysomatic T–O–T (biopyribole) and H–O–H structures

Abstract: Aspects of the bond topology and chemical composition of a mineral may be incorporated into a general formula by writing the local topological details of each cation and anion, along with their chemical identity, as a general expression called a structure-generating function. Here, this procedure is described for polysomatic TÀOÀT and HÀOÀH structures. We may write tetrahedrally coordinated cations and their associated anions as {T 2n Y m }. For {T 2n Y m } to be a chain or ribbon, 5n < m 4 6n, and we may writ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…We may divide these structures into two types: (1) those that involve different stacking sequences in the a-direction (C2/m, Pnma and Pnmn), and (2) those that are derivatives of (1) and involve differences in coordination (P2 1 /m) and/or topochemistry (P2/a or C1) . Complete details of the amphibole structure and chemistry are given in and Oberti et al (2007), and Hawthorne (2012b) and mica supergroups) and HOH (astrophyllite, nafertisite, veblenite and mica supergroups) minerals via (algebraic) generating functions.…”
Section: T 3 T Chains and Ribbonsmentioning
confidence: 99%
“…We may divide these structures into two types: (1) those that involve different stacking sequences in the a-direction (C2/m, Pnma and Pnmn), and (2) those that are derivatives of (1) and involve differences in coordination (P2 1 /m) and/or topochemistry (P2/a or C1) . Complete details of the amphibole structure and chemistry are given in and Oberti et al (2007), and Hawthorne (2012b) and mica supergroups) and HOH (astrophyllite, nafertisite, veblenite and mica supergroups) minerals via (algebraic) generating functions.…”
Section: T 3 T Chains and Ribbonsmentioning
confidence: 99%
“…Let it be understood that each of these questions below is addressed to the sheet-silicate minerals: Why is the 6 3 net so dominant a motif?Why is the net 3.12 2 not represented in mineral structures?All 3-connected nets have the stoichiometry [T 2 O 5 ]; what factors dictate which net is used for a specific mineral?Why do lower-valent tetrahedrally coordinated cations prefer 4-connected tetrahedra?Note that u 6 and d 6 rings of tetrahedra tend to occur in minerals with sheets of edge-sharing octahedrally coordinated (usually divalent) cations. Hawthorne (2012 b ) showed that where two parts of an atomic arrangement join, there must be a one-to-one mapping of the apical anions of the sheet of tetrahedra onto the anions of the interstitial complex. This may occur where a 6 3 sheet of tetrahedra links to an O-sheet of octahedra, accounting for the occurrence of u 6 and d 6 rings of tetrahedra in minerals with sheets of edge-sharing octahedra.…”
Section: Codamentioning
confidence: 99%
“…Mixed rings of tetrahedra are associated with interstitial cations of coordinations > [6]. The one-to-one mapping argument of Hawthorne (2012 b ) must hold, and it will be of considerable interest to relate the u–d character of the rings of silicate tetrahedra to the arrangements of the linking interstitial species.Why are many double-layer silicates based on parent nets that do not occur in single-layer structures?What is the relation between minerals with the same connectivity but different dimensions of polymerisation?…”
Section: Codamentioning
confidence: 99%
See 2 more Smart Citations